Implantable Devices for Sustained, Intravesical Drug Delivery - Lee, Seung Ho (Int Neurourol J, 2016)
In clinical settings, intravesical instillation of a drug bolus is often performed for the treatment of bladder diseases. However, it requires repeated instillations to extend drug efficacy, which may result in poor patient compliance. To alleviate this challenge, implantable devices have been developed for the purpose of sustained, intravesical drug delivery. In this review, we briefly summarize the current trend in the development of intravesical drug-delivery devices. We also introduce the most recently developed devices with strong potential for intravesical drug-delivery applications.